Data associated with "Assessing Rain Drop Breakup Parameterizations using Disdrometer Observations" - Saleeby, Stephen; Dolan, Brenda; Bukowski, Jennie (Colorado State University. Libraries, 2022)
An intercomparison of rain drop mean diameter frequency distribution (RDFD) is performed for numerical simulations of precipitating cloud systems using an array of models and microphysics schemes. This includes results from the Regional Atmospheric Modeling System (RAMS) double-moment microphysics, the Hebrew University Cloud Model bin microphysics (HUCM) interfaced to the RAMS parent model, and the Weather Research and Forecasting Model (WRF) with the Thompson, Morrison, Double Moment 6-Class (WDM6), and National Severe Storm Laboratory (NSSL) double-moment schemes. Simulations are examined with respect to the rain drop size distribution (DSD) volume-number mean diameter (Dm) and intercept parameter (Nw). When compared to a suite of disdrometer observations, the RDFD resulting from each microphysics scheme exhibits varying degrees of mean drop size constraints and peaks in the frequency distribution of Dm. A more detailed investigation of the peaked RDFD from the RAMS simulations suggests that the parameterization of rain drop collisional breakup can impose strong limitations on the evolution of simulated drop growth. As such, a summary and comparison of the drop breakup parameterizations among the forementioned microphysics schemes is presented. While some drop breakup parameterizations are adjusted toward the observations by modifying the threshold diameter for the onset of breakup, this study explores the use of a modified maximum breakup efficiency. This method permits the parameterization to retain its threshold breakup diameter, while limiting the strength of drop breakup and permitting a broader range of drop sizes. As a result, the simulated mean drop sizes are in better agreement with observations.
The data contained herein are the post-processed disdrometer observational data and numerical simulation data. Python Jupyter notebooks are included that were used to process the raw data and to run the analyses and plotting includes herein. The README files describes each included tar file in more detail. The actual raw observational data and model data are too large to include in the repository, but the model namelist files are included that could be used to reproduce the model output. The post-processed data that can be reanalyzed and plotted are included since they are within the space limitation.
Department of Atmospheric Science
Keywords: Disdrometer rain drop data; Numerical Weather Simulations